CO2 Emission, Energy Consumption and Economic Development in Malaysia - Muhyidin, Hamizah bt; Saifullah, Md. Khaled; Fei, Yap Su (International Journal of Management Excellence (ISSN: 2292-1648), 2015)
Environmental awareness and its relation to the development of economy have garnered increased attention in recent years. This study analyzes the long-run relationship between environment degradation, economic growth, total energy consumption and industrial production index growth in Malaysia from year 1970 to 2012. The time series data are estimated using Johansen and Julies Cointegration test and VECM Granger causality test. The empirical analysis suggests a long-run cointegration relationship between all series. Granger causality analysis indicates strong evidence of uni-directional Granger causality running from economic growth and industrial production index growth to total energy consumption in the long-run. Also, the result shows evidence of a bi-directional Granger causality between total energy consumption and CO2 emission. This situation suggests that a pollution abatement policies and higher investment to control for CO2 emission will not jeopardize the economic sustainability and industry output in the long run. This study suggests that previous policies should be complimented with increasing the efficiency of energy use by employing a fuel balancing strategies and promoting the use of renewable energy resources like bio-fuel, solar energy and wind.